Relación de la caries dental con índice de masa corporal de niños 5-12 años de edad de las comunidades rurales de la parroquia Cangahua, Ecuador - Hernández Cadena, Andrea Belén (2017)
Nutrition is an essential factor in the growth and development of the human being, this depends to a great extent on the state of health. Nutritional deficiencies in children delay physical, mental and learning processes. Children in indigenous communities are more prone to nutritional deficiencies due to different social determinants. Children with malnutrition or obesity are at increased risk of acquiring diseases of the oral cavity because studies indicate that the Body Mass Index is directly related to dental caries The objective of the present study was to establish the relationship between body mass index (BMI) and dental caries index CPOD / ceod in 140 indigenous girls aged 5 to 12 years in the Cangahua community. Obtained the weight and height of each child with which the body mass index was obtained and to determine the prevalence of caries needed to obtain the CPOD and ceod indexes the results of this study did not find a statistically significant relationship between BMI and dental caries in children in the Cangahua community. Regarding the DMFT index, only 3 percent of the children presented a high risk of dental caries, whereas only 7 percent of the children presented a high and very high risk of dental caries. In addition, it was determined that only 2.1 percent of children presented obesity and also 2.1 percent presented malnutriti